What is Hidden, in the Hidden Economy of Pakistan? Size, Causes, Issues, and Implications (The Pakistan Development Review, 2010)
The informal economy is initially considered as the subsidiary sector in terms of its contribution to the overall economy. However, it received the focus of attention with the publication of Peter Guttmann’s estimates for sizing the informal economy (i.e. US $ 200 billion in 1976) for the US economy especially in the context of achieving the goal of inclusive growth and development. The informal economy is recognised with different names in different countries/regions throughout the world. For example, the Swedish and Russian term it as ―Hidden Economy‖, the English call it ―Fiddle‖, the Japanese recognise it as ―Hidden Incomes‖, the French identify it as ―Travail au noir‖, the Italian consider it as ―The Lavorno Nero‖, while in Pakistan it has been analysed as an ―Hidden Economy‖ or ―Informal Economy‖.